Self-powered mobile sensor for in-pipe potable water quality monitoring - Wu, L.; Wan Salim, Wan Wardatul Amani; Malhotra, Shweta; Brovont, Aaron D.; Park, Joonhyeong; Pekarek, Steven V.; Banks, Margaret Katherine; Porterfield, D. Marshal (Chemical and Biological Microsystems Society, 2013)
Traditional stationary sensors for potable-water quality monitoring in a wireless sensor network format allow for continuous data collection and transfer. These stationary sensors have played a key role in reporting contamination events in order to secure public health. We are developing a self-powered mobile sensor that can move with the water flow, allowing real-time detection of contamination in water distribution pipes, with a higher temporal resolution. Functionality of the mobile sensor was tested for detecting and monitoring pH, Ca2+, Mg2+, HCO3-/CO32-, NH4+, and Clions. Moreover, energy harvest and wireless data transmission capabilities are being designed for the mobile sensor.